Performance of community resources indicators for tourism development: a case study of Mah Meri community in Carey, Island, Malaysia - Kunasekaran, Puvaneswaran; Gill, Sarjit S.; Ramachandran, Sridar; Talib, Ahmad Tarmizi; Prabhakaran, Sudesh (IDOSI Publications, 2017)
This paper presents the significant role of community resources which is utilized by the Mah Meri community in Pulau Carey, Malaysia to practice sustainable tourism. Mah Meri is one of the 18 indigenous tribes in Peninsular Malaysia that resides at Kampung Sungai Bumbon which is a well established indigenous tourism destination in Malaysia. Survey which was used as the qualitative data collection method helped the researchers to understand the community resources which can encourage sustainable tourism practice. Community resources consisting of cultural, natural, infrastructure, financial and human resources were tested. This study reveals that the community is proud of its natural and cultural resources. However, the community also feels that their tourism business is facing a threat because of scarcity of necessary natural resources. It is hoped that the findings of this study will contribute to existing literature in the indigenous tourism ground that could improve the sector into a more beneficial source of income for the indigenous community.